2014
DOI: 10.1111/prd.12053
|View full text |Cite
|
Sign up to set email alerts
|

Short implant in limited bone volume

Abstract: Rehabilitation of severely resorbed jaws with dental implants remains a surgical and prosthetic challenge for clinicians. The purpose of this review was to evaluate the available data on short-length implants and discuss their indications and limitations in daily clinical practice. A structured review of MEDLINE and a manual search were conducted. Thirty-two case series devoted to short-length implants, 14 reviews and 3 randomized controlled trials were identified. Of this group of papers, we can conclude that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
99
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 81 publications
1
99
1
6
Order By: Relevance
“…This could be due to the poor bone quality in which some of the implants were placed. Some authors suggest that lower quality of bone is associated with a higher failure rate [31] which is true in areas like the posterior maxilla or augmented bone [32,33] so it would be expectable that the results of this SR presented higher failure rates when comparing to standard implants placed in native bone. However, two recently published meta-analysis reported annual failure rates between 2 and 3% [34,35] that are well within the values obtained in this systematic review for short implants and standard implants in augmented bone.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the poor bone quality in which some of the implants were placed. Some authors suggest that lower quality of bone is associated with a higher failure rate [31] which is true in areas like the posterior maxilla or augmented bone [32,33] so it would be expectable that the results of this SR presented higher failure rates when comparing to standard implants placed in native bone. However, two recently published meta-analysis reported annual failure rates between 2 and 3% [34,35] that are well within the values obtained in this systematic review for short implants and standard implants in augmented bone.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the placement of implants of reduced length (4-8.5 mm) represents a less complex surgery, with a reduced cost and morbidity, overall treatment time and high implant survival rate. 3,4 Currently, there is no evidence of superiority of one technique over the other. High implant and prosthesis survival rates for both short implants (SIs) and standard length implants in association with sinus lift were reported in several medium-short term clinical studies [5][6][7][8][9][10][11] and systematic reviews.…”
Section: Introductionmentioning
confidence: 99%
“…1 This solution represents an alternative to more invasive surgeries such as bone grafting, guided bone regeneration, distraction osteogenesis or lateralization of the alveolar nerve. 2,3 The definition of short implants is still non -consensual among authors. Some consider a short implant when its length is shorter than 10 mm, 1,4,5 while other authors propose 8 mm as the maximal length to define a short implant.…”
Section: Introductionmentioning
confidence: 99%
“…A similar behaviour was found by Himmlová et al 24 Although not considered statistically significant, the resonance frequency analysis performed by Calvo -Guirado et al 25 showed that the ISQ values for short implants were lower than those found for longer implants. Nisand et al, 3 explained the possible failure of short implants with a reduced implant primary stability, bone -to -implant contact, as well as an unfa-vourable crown -to -implant ratio. Biomechanical studies highlight the danger represented by the bending loads either for short implants, once they have a smaller area to dissipate tensions, 2,26 or for cortical bone because its yield strength is lower when the load is acting on a perpendicular direction to its major axis.…”
Section: Introductionmentioning
confidence: 99%